Emerging Social Enterprise Ecosystems is East and South African Countries : A Diagnosis of Supporting Environments and Activity of Social Enterprises in Kenya, Malawi, Rwanda, South Africa, Tanzania, Uganda, and Zambia - Navarrete Moreno, Cristina (World Bank, Washington, DC, 2017)
Across Sub-Saharan Africa millions of people remain excluded from critical, life-enhancing services, such as access to water, energy, sanitation, education, and health care. As a result, approximately 600 million Africans lack access to electricity, while life expectancy and literacy are at their lowest rates globally. Moreover, inequality of access to these basic services remains a challenge, especially for marginalized groups, such as women and the rural and urban poor. In this context, Social Enterprises (SEs) have emerged as a new type of development actor with the potential to help solve the service delivery gap. SEs are privately owned organizations,,either for-profit, non-profit, or a hybrid of the two, that use business methods to advance their social objectives. The first part of the report presents an overview of the current landscape for SEs in Kenya, Malawi, Rwanda, South Africa, Tanzania, Uganda, and Zambia. The second part introduces the SE ecosystem and provides a diagnosis of current ecosystems across the seven countries. The report highlights cross-country findings based on research at three levels: the country level, service sector level, and specific service level (Figure 2). Seventeen studies focus on health, water and sanitation, education, and energy sectors at the country level, and five studies focus on specific services, such as maternity care and HIV prevention at the country level. The report targets development practitioners involved in policy design and implementation who are interested in new ways to address service delivery challenges. These specific examples of challenges and opportunities for SEs in Africa can highlight ways to increase the sustainability and scale of current and future SE business models.